2013
DOI: 10.1016/j.neuropsychologia.2013.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention: Differential shifts in pseudoneglect direction with time-on-task and initial bias support the idea of observer subtypes

Abstract: Asymmetry in human spatial attention has long been documented. In the general population the majority of individuals tend to misbisect horizontal lines to the left of veridical centre. Nonetheless in virtually all previously reported studies on healthy participants, there have been subsets of people displaying rightward biases. In this study, we report differential time-on task effects depending on participants' initial pseudoneglect bias: participants with an initial left bias in a landmark task (in which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 56 publications
7
57
3
Order By: Relevance
“…For each task stimulus length was pseudo-randomised -each stimulus length could not be repeated more than twice in a row. A consistent finding is that pseudoneglect does not seem to be driven by any one strategy (Varnava & Halligan, 2009;Voyer, Saint-Aubin & Cook, 2014), though time on task may be influential (Benwell, Thut, Learmonth & Harvey, 2013), so we did not ask participants to use any one strategy with the exception of mental number line bisection (as described below).…”
Section: Methodsmentioning
confidence: 91%
“…For each task stimulus length was pseudo-randomised -each stimulus length could not be repeated more than twice in a row. A consistent finding is that pseudoneglect does not seem to be driven by any one strategy (Varnava & Halligan, 2009;Voyer, Saint-Aubin & Cook, 2014), though time on task may be influential (Benwell, Thut, Learmonth & Harvey, 2013), so we did not ask participants to use any one strategy with the exception of mental number line bisection (as described below).…”
Section: Methodsmentioning
confidence: 91%
“…Decreasing vigilance is believed to be involved in changes in other attentional effects. Manly, Dobler, Dodds, and George (2005) reported that reduced vigilance due to a time-on-task effect is associated with a reduction in natural attentional biases to the left side (although see Benwell, Thut, Learmonth, & Harvey, 2013, for a more specific effect). Matthias et al (2009) used a 50-min vigilance-taxing task to reduce alertness followed by a partial-report paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from experiment 2 of Benwell et al (2013b), the paradigm represented a computerized version of the landmark task (Milner et al, 1992; McCourt and Olafson, 1997; Olk and Harvey, 2002). Lines of 100% Michelson contrast were presented on a gray background (luminance = 179, hue = 179).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, rightward spatial biases are often associated with states of both tonic and chronic reduced arousal (Bellgrove et al, 2004; Manly et al, 2005; Fimm et al, 2006; Dufour et al, 2007; Dodds et al, 2008; Heber et al, 2008; Matthias et al, 2010; Benwell et al, 2013a,b; Newman et al, 2013). It is possible that a reduction in general alertness/vigilance over the lifespan (Robinson and Kertzman, 1990; Buysse et al, 2005; Nebes et al, 2009; Goedert et al, 2010) may also contribute to the chronic attenuation of pseudoneglect in the elderly.…”
Section: Introductionmentioning
confidence: 99%